Enantioselective synthesis of tarchonanthuslactone via iterative hydrolytic kinetic resolution - Gupta, P; Naidu, SV; Kumar, P (Tetrahedron Letters, 2005)
A short and practical enantioselective synthesis of tarchonanthuslactone has been achieved in high diastereomeric excess using iterative Jacobsen's hydrolytic kinetic resolution and ring closing metathesis as the key steps. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Jacobsen's hydrolytic kinetic resolution; Ring closing metathesis; tarchonanthuslactone